2003
DOI: 10.1046/j.1460-9592.2003.00084.x
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of Pacemakers and Implantable Cardioverter Defibrillators in Orally Anticoagulated Patients

Abstract: The safety of pacemaker and defibrillator implantations in orally anticoagulated patients using standard techniques has not been thoroughly evaluated. This article describes a prospectively collected experience in such patients. Patients presenting for device implantation who were treated with warfarin were allowed to continue therapy provided that the INR was < 3.5. Implantations involved cannulation of the left axillary vein. Except for defibrillator leads, 7 Fr introducers were used, and all were leads acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 22 publications
2
43
0
Order By: Relevance
“…2,11,14 Strategically, an ongoing warfarin approach shifts the potential risk of adverse outcomes toward bleeding and away from thrombosis in the perioperative period. Conceptually, the high bleeding risk is present during surgery in patients who remain on warfarin, facilitating immediate recognition and therefore appropriate management of ongoing bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,11,14 Strategically, an ongoing warfarin approach shifts the potential risk of adverse outcomes toward bleeding and away from thrombosis in the perioperative period. Conceptually, the high bleeding risk is present during surgery in patients who remain on warfarin, facilitating immediate recognition and therefore appropriate management of ongoing bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…1,9 -13 Conversely, safe implantation of devices without interruption of warfarin has been reported. 2,11,14 In the absence of clinical trials to guide practice, we sought to determine the perioperative anticoagulation strategies currently used in Canada to guide the design of a prospective randomized trial.…”
Section: Introductionmentioning
confidence: 99%
“…The present findings suggested that pocket effusion or hematoma caused by an allergic reaction was more serious and harmful when compared with pocket effusion or hematoma caused by other risk factors. Furthermore, previous studies have indicated that no effective treatment for pocket hematoma has been discovered (25). …”
Section: Discussionmentioning
confidence: 99%
“…These complications are associated with prolonged hospitalization, increased hospital charges, slow wound healing, typically result in re-operation and may cause surgery failure (3,4). Furthermore, hematoma may increase the risk of infection and cause endocarditis (35). Therefore, whether pocket hematoma may be prevented and treated would affect the success of pacemaker surgery.…”
Section: Introductionmentioning
confidence: 99%
“…This study strongly supports the association of early heparin use with bleeding complications. • Al-Khadra [34] described a series of 47 patients in whom implantation of a pacemaker or ICD was accomplished with uninterrupted oral anticoagulation. In this series, there were no instances of major bleeding or device-related complications.…”
Section: What Strategies Can Be Used In Patients With Compelling Reasmentioning
confidence: 99%